Analysis and Optimization of Behavioral Parameters of Stiff-ened Steel Plate Shear Walls with Various Opening - Isha Verma, Dr. S. Setia (International Journal of Advanced Science and Technology, 2020)
Due to better seismic behavioral properties of steel plate shear wall (SPSW) gigantic researchers have shown avid interest in performance of SPSW for numerous structural building. Although because of assertive architectural demand it becomes pressing to introduce openings also to accommodate the load rebellion behavior of building structures. In this paper FEA (Finite Element Analysis) is done in steel plate shear wall using various opening with cross stiffeners. In this study a static analysis is conducted in ANSYS workbench using FEA analysis for stimulation of various parameters buckling loads, stresses and deformation for both types of opening. It is also found that there is difference of 1.79% buckling load for SPSW with rectangular opening type as compared to circular opening. The response surface optimization is also done for analysis of behavioral characteristics and sensitivities with different optimization parameters and its influence on output parameters. Keywords: SPSW, Openings, FEA, ANSYS, Response surface optimization